REFERENTIAL OR POETIC? CONTRIBUTION TO THE STUDY AND PRACTICE OF AUDIODESCRIPTION AS AN ART FORM - Chorão, Graça (2019)
Since 2007, there has been a systematic research conducted in the field of Audiovisual Translation (AVT) at ISCAP/ Porto Polytechnic Institute. At the time we embarked on a research endeavor focusing on audio description (AD), with the intent of systematizing AD guidelines, improving the AD process and reflecting on teaching/learning methods. This study presented at the Media For All conference, Antwerp, in 2009, aims to contribute to this project by focusing on issues linked to the generalized view that AD language should be ‘objective’ and therefore referential in nature, as stated in several guidelines. Indeed, the audio describer is even warned against expressing emotions or personal points of view. How seriously is this advice taken? Is this in fact what we should be teaching and doing? Are there identifiable common language functions in AD and are these clearly portrayed in the existing guidelines? In order to answer these questions, we assess the BBC Guidelines on the provision of television access services; the Audio Description International’s AD Guidelines Draft; the American Council of the Blind’s Audio Description Standards; the now extinct ITC Guidance on Standards for Audio Description; the Audio Description Coalition Guidelines for Audio Description, listing and contrasting their recommendations as to the ‘how’ and the ‘what’ of AD. Next, we compare these findings with randomly selected audio described feature films pertaining to the genres of drama, action, and suspense, namely Blindness, Revolutionary Road, The Happening, Body of Lies, The Eye, and Hancock. After analyzing both AD segments and movie clips in terms of visual rhetoric and Jakobson’s language functions, we propose that described movies stretch the concept of intersemiotic translation.